2016
DOI: 10.1055/s-0042-110933
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic endoscope imaging for routine colonoscopy: impact on propofol dosage and patient safety – a randomized trial

Abstract: The use of MEI may be useful in reducing propofol dosage for colonoscopy and improving patient satisfaction.ClinicalTrials.gov identifier: NCT02121704.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It involved patients who were given “conscious sedation” using midazolam and fentanyl as compared to a growing trend of performing these procedures under deep sedation using propofol administered by anesthesia professionals 13 . Despite moderate sedation, the outcomes were within the scope of a traditional practice with fewer side effects and reasonable patient satisfaction scores achieving good standard-of-care quality measures, which is in comparison to another study that showed lower doses of propofol in the MEI group 14 . Use of deep sedation can limit position changes.…”
Section: Discussionmentioning
confidence: 59%
“…It involved patients who were given “conscious sedation” using midazolam and fentanyl as compared to a growing trend of performing these procedures under deep sedation using propofol administered by anesthesia professionals 13 . Despite moderate sedation, the outcomes were within the scope of a traditional practice with fewer side effects and reasonable patient satisfaction scores achieving good standard-of-care quality measures, which is in comparison to another study that showed lower doses of propofol in the MEI group 14 . Use of deep sedation can limit position changes.…”
Section: Discussionmentioning
confidence: 59%
“…Data on magnetic imagers have been available for over 20 years, but only recently did the largest meta-analysis to date come down in favour of their use for reducing time to caecum (even in expert hands), increasing caecal intubation rate and reducing pain scores 10 . A more recent unblinded study 11 of propofol usage in a colonoscopy population was able to demonstrate increased satisfaction scores and reduced propofol use with a magnetic imager, and as a further study has demonstrated that propofol-supported colonoscopy is associated with higher complication rates 12 , it is interesting to hypothesise that a suitably powered study could demonstrate improved safety as well. The most exciting contribution to improvements in colonoscopic insertion technique has been the advent of water-assisted insertion techniques.…”
Section: Colonoscopy Insertionmentioning
confidence: 98%
“…P aediatric ileo-colonoscopy (IC) can be technically challenging because of unpredictable colonoscope loop formation mainly in the sigmoid and transverse colon. The magnetic endoscope imaging (MEI) tool (ScopeGuide, Olympus, America, Inc, Allentown, PA) (1,2) is a non-radiographical technique for picturing the colonoscope shaft in real time (3)(4)(5) and it represents a useful tool for training purposes (6). Studies on loop formation have been published in adults (7)(8)(9) but no studies so far have been conducted in paediatric IC.…”
mentioning
confidence: 99%